1977
DOI: 10.1002/maco.19770281104
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Products Formed on Copper exposed to humid SO2‐containing atmospheres

Abstract: X‐ray diffraction analyses have been performed on samples of electrolytic copper (min. 99,9% Cu) exposed to humid atmoshperes at SO2‐supplies of 10 and 100μg SO2 per cm2 surface area per hour (10 and 100 ppm SO2. respectively). During the SO2 ‐exposures copper (II) sulphate (CuSO4 · 5 H2O) were the only crystalline phases formed in detectable amounts. Interruption of the SO2‐ supply resulted in the formation of copper (I) oxide and antlerite (CuSO4) · 2Cu (OH)2. During prolonged exposure brochanite (CuSO4 · 3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Laboratory chamber tests using corrosive gases such as sulfur dioxide under humid conditions have been performed to understand the corrosion behavior of copper. [4][5][6] Chamber test results showed that nitrogen dioxide and ozone present in the atmosphere accelerated copper corrosion through the effect of sulfur dioxide. Even with an extremely low sulfur dioxide concentration of, for example, 5 ppb, a black patina forms on a copper surface when the relative humidity exceeds 85%.…”
mentioning
confidence: 99%
“…Laboratory chamber tests using corrosive gases such as sulfur dioxide under humid conditions have been performed to understand the corrosion behavior of copper. [4][5][6] Chamber test results showed that nitrogen dioxide and ozone present in the atmosphere accelerated copper corrosion through the effect of sulfur dioxide. Even with an extremely low sulfur dioxide concentration of, for example, 5 ppb, a black patina forms on a copper surface when the relative humidity exceeds 85%.…”
mentioning
confidence: 99%
“…Although many laboratory studies have been made of atmospheric copper corrosion in an environment with a high concentration of corrosive gases, [16][17][18][19][20][21][22] few have focused on corrosion behaviour in an actual environment with a high H 2 S concentration. 23 In the study reported here, we investigated atmospheric corrosion of copper exposed indoors and outdoors in a hot springs area.…”
Section: Introductionmentioning
confidence: 99%
“…Although the corrosion phenomena of a Cu film in an environment containing sulfur or chlorine are well known, [6][7][8][9][10][11] in the CMP process, we have discovered that the Cu etching rate can be enhanced without affecting the pH by adding a small amounts of sulfur compounds to the slurry.…”
Section: Introductionmentioning
confidence: 99%